Organisationale Agilität von Buchverlagen: Forschungsstand - Ina Fuchshuber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2020)
– Book Publishing is a high-risk business since book publishing houses need to drop most of their product range every half of the year and create new titles. Planning success therefore is a very hard thing to do and is stated as "erratic". In addition Book publishing houses not only aim at economic success but also at creating culture. These special con- ditions have led to the demand of a dual organisation with efficient, hierarchical business processes on the one hand and decentralized, non- hierarchical creatives processes on the other. However, there has been no real discussion in media management literature how this should be achieved and how those both systems can work together effectively in one company. Furthermore Book Publishing has seen tremendous shifts in the last years: With customer behaviour and media consumption habits changing more quickly than ever book publishing needs to be more customer oriented while media convergence and the demand for content in a multitude of formats (e.g. printed books, apps, E-Books, websites) are demanding new and flexible organisational answers. A possible approach for finding new and adaptable practices is the concept of organizational agility, which was created for companies in highly- innovative and fast changing environments in manufacturing in the 1970ies and lived up to widespread use in IT-companies and IT-related research accordingly since the 1990ies and during the 2000s. This Literature Review aims at summarizing the status of organizational research in the media economy and especially the book publishing eco- nomy as well as describing the status of organizational agility in research both from a manufacturing and IT-management view. It shows that the organizational perspective on book publishing lacks research and opens the question if and how organizational agility and agile frameworks can help book publishing houses to maintain and gain adaptability.
urn:nbn:de:bvb:29-opus4-133619
Keywords: 330; Agilität; Ambidextrie; Buchverlag; Duale Organisation; organisationale Agilität